Association between urinary heavy metal mixtures and overactive bladder risk in the U.S. adult population: a cross-sectional study - Liu, Zhenzhen; Guo, Zikai; Su, Husong; Xue, Sheng; Xiong, Bing (Frontiers in Public Health, 2025)
The existing body of literature consistently underscores the adverse health implications associated with exposure to toxic metals among humans. There is still a substantial knowledge gap about how concurrent exposure to metal combinations affects the prevalence of overactive bladder (OAB). Our detailed examination focused on the complex associations between simultaneous heavy metal exposure and OAB in adults. By utilizing data from 7,719 adults in the National Health and Nutrition Examination Survey (NHANES), we assessed both individual and combined effects. From all participants, 1,574 (20.39%) were diagnosed with OAB. The research found that elevated urinary levels of cadmium, cobalt, lead, and antimony were associated with a higher risk of OAB. Conversely, urinary barium exhibited a noteworthy protective effect against OAB. Additionally, the weighted quantile sum regression and BKMR models consistently underscored the positive influence of being exposed to multiple urinary metals at the same time on the risk of OAB. The impact was more evident among young and middle-aged people and those who have consumed alcohol, as opposed to older adults and abstainers. The BKMR analysis additionally unveiled potential interactions among specific components of metal mixtures contributing to OAB. The g computation model based on quantiles verified the harmful impacts of metal combinations on OAB. Furthermore, the risk of OAB was positively correlated with Cd and Co, as revealed by restricted cubic spline regression. The research reveals that being exposed to various heavy metals simultaneously significantly boosts the risk of OAB. To thoroughly validate these results, prospective studies are essential due to the limitations of the NHANES study design.